Z dokazi podprta habilitacija otrok s cerebralno paralizo - Damjan, Hermina (Rehabilitacija (Ljubljana), 2010)
Cerebral palsy denotes as a group of long-term disorders of the development of child's movement and posture, often accompanied by disturbances of sensation, cognition, communication, speech, feeding and/or behaviour, and/or by a seizure disorder. Children with cerebral palsy are very heterogeneous group regarding both aetiology and consequences in terms of disabilities, functioning and participation. The paper presents the results of studies and systematic reviews analysing the efficiency of therapeutic programmes for children with cerebral palsy in clinical practice, i.e., physiotherapy, occupational therapy with emphasis on constrained induced therapy, provision of orthoses, speech therapy, spasticity treatment using botulinum toxin and baclofen, and functional electrical stimulation.
Keywords: cerebralna paraliza; child; otroci; rehabilitacija; terapevtski programi; therapy; vocational rehabilitation; zdravljenje